OBOWIĄZEK NIEWOLNIKÓW OBRONY SWOJEGO WŁAŚCICIELA - Loska, Elżbieta (Zeszyty Prawnicze, 2017)
Slaves’ Duty to Defend Their Owners Summary Romanist doctrine speaks about legal regulations providing for slaves’ obligation to bring help to their owners (SC Silanianum from 10 A.D. and SC Neronianum as well as SC Pisonianum from 57 A.D.). Whereas the majority of the researches discuss the civil aspect of this obligation, the senatus consulta could also have had a criminal nature, in particular they could have regarded a self-defense issue. SC Silanianum from 10 A. D. ordered to torture slaves and punish them with death if they had not brought help to their owners, who - as a consequence - were killed: it means that slaves who stayed under one roof or who traveled with the owner were to bring him help at any price. Two subsequent resolutions extended the regulations of SC Silanianum. It transpires from the available sources that slaves could use any means which might turned out to be effective - if shouting or calling for help did not suffice, slaves should use other available means to repulse an attack. It seems that slaves were treated as the owner’s piece of weapon. This resembles one of the conditions of the contemporary law which is necessary to evaluate whether a person acted in a self-defense: this is a reaction against an attack aiming at an effective repulsion, with a use of indispensable measures. Slaves were punished even with death if they had not stood up for their owner in certain circumstances. On this basis, one may come to a conclusion that defending the owner was one of the slaves’ duties. Catching a wife in flagranti on adultery was one of the exceptions: slaves were not obliged to defend her, most probably because she was not expected to defend herself as well. In case of a suicide, the slaves were obliged to act only if dominus tried to commit a suicide at their presence and even if their defense was not successful they were rarely punished. Therefore, it seems that the slaves’ actions were not to prevent the owner from death; the slaves were just obliged to defend him against third persons. On the basis of SC Silanianum,slaves who did not manage to prevent their owner from death of poisoning or as a result of a trap were not punished as well. Senate’s resolutions were aimed not only at punishing the slaves who did not stand up for their owner but were also to clearly indicate in what circumstances they should defend their owners. They were responsible for non-acting or acting ineffectively only when their dominus had the right to defend himself.